FarmRec: 'n geïntegreerde ekstensiewe veeboerdery rekordhoudingstelsel - Theron, Johannes Frederick (University of the Free State, 2003)
Extensive farmers in South Africa do not generally keep records of their farming activities, and if they do, it only entails financial record keeping for the Receiver of Revenue. Resources for farm record keeping, especially with regard to grazing and animals, are scarce, and the systems that do exist are elementary. Those farmers who do keep records make use of various approaches, ranging from manual and paper-based systems and computer spreadsheets, to specialist software for certain aspects oftheir farming activities. The FarmRec record-keeping system was developed to provide for a wide range of livestock farming activities. With the development of this record-keeping system, existing shortcomings and problems were addressed, taking into consideration all aspects to be included and contained in a record-keeping system in order to provide a purposeful, comprehensive and user-friendly product. Various information categories are integrated in this system, thereby negating the need for several different types of record-keeping systems. The main purpose of record keeping is to gather information from one's own data. The need for specific information makes it necessary for records to be kept of certain resource data. The relation between resources and the information obtained from them is comprehensively discussed. This relation also indicates the flow of data and information between resources. The FarmRec system was designed and developed around these relations. The waterfall and evolutionary development processes were used to develop and test the system, and to make corrections and improvements to the system. By means of this system, records are kept of information relating to paddocks, land, grazing, animal numbers and animal management actions, as well as of animal and plant product quality and quantity, income and cost information, infrastructure, and financial and rainfall information pertaining to the farming unit. The information to be provided for the different record-keeping facets is discussed. Attention is also given to the integration of information. The information is made available in the form of reports. The extent to which these reports are available is determined by the degree to which the user entered the data of the different facets into the computer. This system makes a large number of reports available to the user. The type of report is determined by the grouping of the selected data. The user himself/herself determines the selection criteria, which consist of the reporting period or date, subunit, groupings and sorting order, as well as level of detail in the report. The system was provided to users and then evaluated to gain an indication of the ease with which the functions and reports in the system can be used. From the evaluation it can be deduced that the FarmRec system is user friendly and easy to use. The system offers many more functions and reports than needed or used by any individual user, but the diversity of users means that different combinations of functions and reports are needed. The level of use by users also varies considerably. With the exception of a few isolated reporting functions, respondents indicated that the functions in the system are easy to use and of much value. The FarmRec system succeeds in addressing a wide range of record-keeping facets. The users indicated that the magnitude and integration are more than sufficient. The system resulted in an improvement in the keeping of grazing records - an aspect that otherwise went unrecorded. Record keeping in respect of grazing was made possible for the user by means of simple notes on animal movement. The total record keeping of the users furthermore improved from their original record-keeping systems. The improvement in record keeping occurred without the users having to spend more time on record keeping. This is regarded as a very positive reaction, as many users indicated that the time available for record keeping is extremely limited.

Ekstensiewe veeboere in Suid-Afrika hou oor die algemeen nie rekord van hul boerderyaktiwiteite nie. Indien wel rekord gehou word, is dit finansiële rekordhouding vir die Ontvanger van Inkomste. Hulpmiddels vir boerdery rekordhouding, veral van beweiding en diere, bestaan nie, en indien wel, is die stelsels gebrekkig. Die boere wat wel rekord hou, maak gebruik van 'n verskeidenheid benaderings wat wissel van hand en papier, rekenaarspreivelle tot spesialis sagteware vir sekere aspekte van hul boerderye. Die FarmRec-rekordhoudingstelsel is ontwikkel om te voldoen aan 'n wye reeks veeboerdery toestande. Met die ontwikkeling van die rekordhoudingstelsel is die bestaande tekortkominge en probleme aangespreek, met inagneming van die aspekte wat in 'n rekordhoudingstelsel opgeneem en vervat moet word, om 'n doelgerigte, omvattende en gebruikersvriendelike produk daar te stel. Met die stelsel is verskeie inligtingskategorieë geïntegreer wat die noodsaaklikheid vir verskillende rekordhoudingstelsels onnodig maak. Die hoofdoel van rekordhouding is om inligting uit eie data te verkry. Die behoefte na spesifieke inligting noodsaak dat rekord gehou word van sekere hulpbrondata. Die verwantskap tussen hulpbronne en die inligting wat daaruit verkry kan word, word breedvoerig uiteengesit. Hierdie verwantskappe dui dan ook die vloei van data en inligting tussen hulpbronne aan. Die FarmRecstelsel is rondom hierdie verwantskappe ontwerp en ontwikkel. Die waterval en evolusionêre ontwikkelingsprosesse is gebruik om die stelsel te ontwikkel, te toets, korreksies asook verbeteringe daaraan aan te bring. Met die stelsel word rekord gehou van kamp-, land-, beweiding-, dieregetalle- en dierebestuursaksie-inligting, asook dierlike- en plantprodukkwaliteit-, kwantiteit- en inkomsteen koste-inligting, infrastruktuur- en finansiële en reënvalinligting van die boerdery-eenheid. Die inligting wat vir die verskillende rekordhoudingfasette voorsien moet word, word bespreek. Aandag is ook gegee aan die integrasie van inligting. Die inligting word in die vorm van verslae beskikbaar gestel. Die mate waartoe hierdie verslae beskikbaar is, word bepaal deur die mate waartoe die gebruiker die data van die verskillende fasette ingelees het. In die stelsel is 'n groot aantal verslae tot die beskikking van die gebruiker. Die tipe verslag word bepaal deur die groepering van die geselekteerde data. Die gebruiker bepaal self die seleksiekriteria, wat bestaan uit die verslagperiode of -datum, subeenheid, groeperings- en sorteringsorde en vlak van detail in die verslag. Die stelsel is aan gebruikers beskikbaar gestel en geëvalueer om 'n aanduiding te kry van die gemak waarmee die funksies en verslae in die stelsel gebruik word. Uit die evaluering kan afgelei word dat die FarmRec-stelsel gebruikersvriendelik en maklik is om te gebruik. Die stelsel bevat baie meer funksies en verslae as wat deur 'n individuleie gebruiker benodig word of gebruik word, maar die uiteenlopendheid van die gebruikers lei daartoe dat verskillende kombinasies van funksies en verslae gebruik word. Die vlak van gebruik deur gebruikers verskil aansienlik. Met die uitsondering van enkele verslagfunksies het die respondente aangedui dat die funksies in die stelsel maklik gebruik en van baie waarde geag word. Die FarmRec-stelsel slaag daarin om 'n breë front van rekordhoudingfasette aan te spreek. Die gebruikers het aangedui dat die omvang en integrasie meer as voldoende is. Die stelsel het ook verder die weidingrekordhouding verhoog, wat andersins glad nie van rekord gehou was nie. Die weidingrekordhouding is vir die gebruiker moontlik gemaak deur eenvoudige diereverskuiwingsaantekeninge. Die totale rekordhouding van die gebruikers het verder verbeter vanafhul oorspronklike rekordhoudingstelsel. Die verbetering in rekordhouding het plaasgevind sonder dat die gebruikers meer tyd aan rekordhouding moes spandeer. Dit is 'n baie sterk positiewe reaksie, aangesien baie gebruikers aangedui het dat tyd vir rekordhouding beperk is.
Software not available
Thesis (Ph.D. (Animal, Wildlife and Grassland Sciences))--University of the Free State, 2003
Keywords: Extensive animal farming; Farm software; Farming software; Grazing record-keeping; Record-keeping software; Record-keeping system; Animal husbandry -- Data processing; Farm management -- Data processing; Management information systems; Farm management -- Records and correspondence